Biogeochemical_Testbed_1.1 (CLM4.5, CRU-NCEP, RCP4.5 & 8.5) - Will Wieder, Wwieder@Ucar.Edu (UCAR/NCAR Climate Data Gateway, 2018)
Data included here include model input data (used to run the biogeochemical testbed), and annually averaged model output (analyzed in Wieder et al. 2018a, b). Input data are daily forcing, ‘met.nc’, files that were generated by the satellite phenology scheme of the Community Land Model (CLM, version 4.5sp; Oleson et al. 2013). Data for the historical period (1901-2010) were generated with atmospheric condition from the CRU-NCEP climate reanalysis data. Data for future scenarios (2011-2100) were generated using an anomaly forcing protocol to replicate a single CCSM4 projection of climate change under both RCP4.5 and RCP8.5 scenarios (Meehl et al. 2012; as in McGuire et al. 2018 and Wieder et al. 2015). Daily output from CLM were modified with the NetCDFTools package developed by Melannie Hartman to generate the met.nc files archived here. These forcing data provide input data needed to run the soil biogeochemical testbed, available here at Will Wieder’s GitHub account https://github.com/wwieder/biogeochem_testbed_1.1. Daily model output from the testbed was averaged annually and analyzed with code available in the ‘analysis_code’ sub-directory of Wieder’s GitHub account. These data include annual mean temperature, soil moisture, and environmental scalars used in the testbed as well as pools and fluxes of carbon in vegetation, litter, soil, and microbial biomass simulated by the CASA-CNP, MIMICS, and CORPSE soil biogeochemical models from 1901-2100 under RCP4.5 and 8.5. More information about the soil biogeochemical testbed and these results are available at W. Wieder’s GitHub page as well as associated publications (Wieder et al. 2018a, b). References: McGuire, A. D. et al. Dependence of the evolution of carbon dynamics in the northern permafrost region on the trajectory of climate change. Proceedings of the National Academy of Sciences, doi:10.1073/pnas.1719903115 (2018). Meehl, G. A. et al. Climate System Response to External Forcings and Climate Change Projections in CCSM4. J Climate 25, 3661-3683, doi:10.1175/jcli-d-11-00240.1 (2012). Oleson, K., Lawrence, D. M., Bonan, G. B., Drewniak, B., Huang, M., Koven, C. D., et al. (2013). Technical description of version 4.5 of the Community Land Model (CLM). NCAR Technical Note NCAR/TN-503+STR. In (pp. 420). doi:10.5065/D6RR1W7M Wieder, W. R., Cleveland, C. C., Lawrence, D. M., & Bonan, G. B. (2015). Effects of model structural uncertainty on carbon cycle projections: biological nitrogen fixation as a case study. Environmental Research Letters, 10(4), 044016. doi: 10.1088/1748-9326/10/4/044016. Wieder, W. R., Hartman, M. D., Sulman, B. N., Wang, Y. P., Koven, C. D., & Bonan, G. B. (2018a). Carbon cycle confidence and uncertainty: Exploring variation among soil biogeochemical models. Glob Chang Biol, 24(4), 1563-1579. doi: 10.1111/gcb.13979. Wieder, W. R., Hartman, M. D., Sulman, B. N., Koven, C. D., & Bradford M. A. (2018b) Arctic systems could drive global losses or gains in soil carbon under climate change. Nature Climate Change. In review